The Philosophy of Realism in Education - Erikawati, Erikawati (Journal of Innovation in Teaching and Instructional Media, 2023)
Realism is a philosophical teaching which considers that a truth is a real picture or a real copy of the world of reality from an idea that exists in someone’s mind. The goal of the philosophy of realism is to understand and recognize the existence of an external world that is objective and independent of the human mind. The philosophy of realism believes that the external world has a real existence and can be accessed through human observation and experience. Another goal of the philosophy of realism is to develop a better understanding of the world and avoid errors in the interpretation and understanding of reality. In the educational context, the philosophy of realism aims to develop education that is based on experience and objective observation, so that students can understand the world better and more accurately.